PEMANFAATAN LANGSUNG SERBUK KULIT KAYU AKASIA SEBAGAI PEREKAT PAPAN PARTIKEL Direct Utilization of Acacia Bark Powder as Adhesive for Particleboard - Subyakto Subyakto; Bambang prasetya (Masyarakat Peneliti Kayu Indonesia, 2003)
Many studies have been done on the utilization of tannin from acacia bark obtained through extraction process for wood composites adhesive. In this experiment, powder of acacia bark was used directly for particleboard adhesive without extraction process to save cost and production-processing time. Acacia (Acacia mangium) bark was powdered into 60 mesh and mixed with wood particles of sengon (Paraserianthes falcataria) with size of 15 mesh. The compositions of wood particles: bark was varied as follows 50:50, 60:40, 70:30, 80:20. Water and paraformaldehyde were added to the mixture. The matt was hot pressed at 180ºC at pressure of 10 kg/cm2 for 15 minutes. The panels were tested for their physical and mechanical properties in accordance with JIS A 5908.The results shown that some physical and mechanical properties of the board with composition of 60 : 40 were met the JIS A 5908 standard. Further studies are needed to improve all the particleboard properties to meet the standard